Perception and discrimination of real-life emotional vocalizations in early blind individuals - Ferrari, Chiara; Arioli, Maria; Atias, Doron; Merabet, Lotfi B.; Cattaneo, Zaira (Frontiers in Psychology, 2024)
The capacity to understand others' emotions and react accordingly is a key social ability.However, it may be compromised in case of a profound sensory loss that limits the contribution of available contextual cues (e.g. facial expression, gestures, body posture) to interpret emotions expressed by others. In this study, we specifically investigated whether early blindness affects the capacity to interpret emotional vocalizations, whose valence may be difficult to recognize without a meaningful context. Specifically, we asked a group of early blind (N=22) and sighted controls (N=22) to evaluate the valence and the intensity of spontaneous fearful and joyful nonverbal vocalizations. Our data showed that emotional vocalizations presented alone (i.e., with no contextual information) are similarly ambiguous for blind and sighted individuals but are perceived as more intense by the former possibly reflecting their higher saliency when visual experience is unavailable. Our study contributes to a better understanding of how sensory experience shapes emotion recognition.